Effect of Dietary Supplementation with Durio zibethinus Murr. cv. Monthong Rind on the Hematology and Innate Immune Response Against Aeromonas hydrophila in Red Tilapia (Oreochromis niloticus x Oreochromis mossambicus) - Duangjai Pisuttharachai; Nataporn Sangkhonkhet; Warrapong Nalinanon; Saichon Lerdsuwan (ASEAN Journal of Scientific and Technological Reports, 2024)
In vivo activity study of durian rind (Durio zibethinus Murr. cv. Monthong) as a supplement in the tilapia diet was performed to evaluate its effect on the hematology and innate immune response against Aeromonas hydrophila. Red Tilapia (Oreochromis niloticus x Oreochromis mossambicus), with an initial average weight range of 40-45 g, were fed diets supplemented with durian rind at 0, 10, 15, and 20% for 140 days and were injected intraperitoneally with A. hydrophila. Blood was collected at 1 and 3 hours post-injection to determine the phagocytic activity and the durian rind efficiency in protecting fish red blood cells from hemolysin produced by A. hydrophila. Ensuing results showed that red blood cell counts in fish-fed durian rind supplemented diets, regardless of inclusion levels, did not decrease at 3 hours post bacterial infection and were significantly higher than control (P<0.05). Furthermore, we observed that the total white blood cells and phagocytic activity of all fish fed with diets supplemented with durian rind increased from 1-hour post-infection, indicating a heightened innate immune response. Taken together, durian rind supplementation of at least 10% in the tilapia diet can act as an immunostimulant and improve innate immune response and anti-hemolytic activity against A. hydrophila infection.
Keywords: Aquaculture disease management and microbiota; Aquaculture Nutrition and Growth; Diverse Scientific Research Studies